Enhancing the ratio of fluorescence to bremsstrahlung radiation in X-ray tube spectra - Távora, L. M. N. (2001)
This paper describes techniques that can be used to improve the ratio of fluorescence to bremsstrahlung radiation (F/B) in X-ray tube spectra. Firstly, an extension of the EGS4 code system is used to evaluate the impact of the substrate in thin target applications, in terms of the yield of bremsstrahlung photons produced. The choice of materials to filter X-ray tube spectra, and its effect in the F/B and the tube efficiency is discussed. The characteristics of spectra produced in transmission tubes with different target thicknesses, substrates and tube voltages are also presented.